PENGARUH CLOSED SUCTIONING TERHADAP PERUBAHAN NILAI HEMODINAMIK NON INVASIF PADA PASIEN YANG TERPASANG VENTILATOR DI RUANGAN ICU RSUD ARIFIN ACHMAD PROVINSI RIAU - Carles Carles; Betty Nia Rulen; Eliza Fitria (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Suctioning is needed in patients who are attached to a ventilator because of the inability to remove secretions independently. The purpose of this study was to determine the effect of suctioning with closed suctioning on non-invasive hemodynamic changes (MAP, heart rate, oxygen saturation and respiratory rate) in patients who are attached to a ventilator. While the research method is quantitative using a pre-experimental research design. The research design uses a one group pre-post test design approach. The research results obtained that the majority of MAP (blood pressure) was 70-100 mmHg, namely 19 people (61.3%), the majority heart rate was 60 -100x/min as many as 16 people (51.6%), while the majority of Oxygen Saturation is 95-100% as many as 25 people (80.6%), and the majority Respiratory Frequency> 12x as many as 26 people (83.9%), while the average effect obtained is mean blood pressure before suctioning.T was obtained at 1.06 and after that at 1.19. Mean Heart Rate before suctioning.T was obtained at 1.35 and after that was 152. Mean Oxygen Saturation before suctioning.T was obtained at 0.81 and after that was 0.94 and the mean Respiration before suctioning.T was obtained at 1.84 and after that at 1.00 With the results of blood pressure analysis before suctioning with a P-value of 0.002. This means that there is a significant effect between the average blood pressure before and after suctioning. The Heart Rate before suctioning with a P value of 0.000. This means that there is a significant effect between blood heart rate before and after suctioning. Furthermore Oxygen Saturation before suctioning with a P value of 0.004. This means that there is a significant effect between Oxygen Saturation before and after suctioning. While Breathing before suctioning with a P value of 0.000. This means that there is a significant effect between breathing before and after suctioning.